a) \(\frac{{ - 2}}{7}:\frac{4}{7} = \frac{{ - 2}}{7}.\frac{7}{4} = \frac{{ - 2}}{4} = \frac{{ - 1}}{2}\)
b) \(\frac{{ - 4}}{5}:\frac{{ - 3}}{{11}} = \frac{{ - 4}}{5}.\frac{{11}}{{ - 3}} = \frac{{ - 44}}{{ - 15}} = \frac{{44}}{{15}}\)
c) \(4:\frac{{ - 2}}{5} = 4.\frac{5}{{ - 2}} = \frac{{20}}{{ - 2}} = - 10\)
d) \(\frac{{15}}{{ - 8}}:6 = \frac{{15}}{{ - 8}}.\frac{1}{6} = \frac{{ - 15}}{{48}}= \frac{{ - 5}}{{16}}\).
a) \(\dfrac{-2}{7}:\dfrac{4}{7}=\dfrac{-2}{7}.\dfrac{7}{4}=\dfrac{-2.7}{7.4}=\dfrac{-1}{2}\)
b) \(\dfrac{-4}{5}:\dfrac{-3}{11}=\dfrac{-4}{5}.\dfrac{-11}{3}=\dfrac{-4.\left(-11\right)}{5.3}=\dfrac{44}{15}\)
c) \(4:\dfrac{-2}{5}=4.\dfrac{-5}{2}=\dfrac{4.\left(-5\right)}{2}=-10\)
d) \(\dfrac{15}{-8}:6=\dfrac{-15}{8}.\dfrac{1}{6}=\dfrac{-15}{8.6}=\dfrac{-5}{16}\)